2020
DOI: 10.1177/0895904820951124
|View full text |Cite
|
Sign up to set email alerts
|

The effects of charter school enrollment losses and tuition reimbursements on school districts: Lifting boats or sinking them?

Abstract: We analyze a natural experiment in which policymakers in Pennsylvania first implemented, and later removed, reimbursements to districts for students exiting to brick and mortar and cyber charter schools. Generalized difference-in-difference models show that larger shares of students enrolling in charter schools predict decrements in spending, financial health, and achievement in sending districts; however, these relationships attenuate in years when districts receive reimbursements. After receiving reimburseme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…Xie and Kang (2009); Wang and Lu (2022). 32 Biasi et al (2021); Khanal (2018); Mann and Bruno (2022). Previous literature has found that economies concentrated in the industry and services sectors have a high demand for skilled human capital.…”
Section: Other Explanatory (Control) Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Xie and Kang (2009); Wang and Lu (2022). 32 Biasi et al (2021); Khanal (2018); Mann and Bruno (2022). Previous literature has found that economies concentrated in the industry and services sectors have a high demand for skilled human capital.…”
Section: Other Explanatory (Control) Variablesmentioning
confidence: 99%
“…On the other hand, the left political ideology exerts a negative impact on enrollment rates (see Column (3) in Table 3), which also suggests the same. It needs 49 see e.g., Biasi et al (2021); Khanal (2018); Mann and Bruno (2022). 50 see Blundell and Bond (1998).…”
Section: Robustness Checksmentioning
confidence: 99%
“…This is an uncommon strategy, but might be a promising model to help district schools adjust to the presence of charter schools in the short term. Work examining a similar district reimbursement policy in Pennsylvania found the financial incentives increased instructional and support services among districts experiencing charter competition (Mann & Bruno, 2020).…”
Section: Financial Impacts Of Charter Schools On District Schoolsmentioning
confidence: 99%
“…The diversity of charter schools makes aggregate analysis suspect. On the other hand, research that focuses on only a single county or district can also be misleading since local contexts and policies may be determining the results (Mann & Bruno, 2022). Additionally, studies also vary in the level of analysis, with many focusing on student-level outcomes.…”
mentioning
confidence: 99%
“…Consistent with a growing body of evidence, our findings suggest that both the competition arguments for improving traditional schools’ performance and diversity and the counter arguments that competition will harm traditional schools’ performance and diversity are off the mark. The discussion might be better aimed at how to make both charter and traditional schools improve their educational programs, perhaps, as indicated by Mann and Bruno (2022) by increasing financial assistance to traditional schools experiencing enrollment losses to charter schools.…”
mentioning
confidence: 99%